Access regulation with asymmetric termination costs - Torben Stühmeier (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2011)
In many telecommunications markets incumbent providers enjoy a demand-side advantage over any entrant. However, market entrants may enjoy a supply-side advantage over the incumbent, since they are more efficient or operate on innovative technologies. Considering both a supply-side and a demand-side asymmetry, the present model analyzes the effect of two regulatory regimes: An access markup for a low cost network and reciprocal charges below the costs of a high cost network. Both regimes may have adverse effects on subscribers, market shares, and profits. It can be shown that an access markup is not generally beneficial and an access deficit not generally detrimental for the respective networks. However, if providers discriminate between on-net and off-net prices a markup on the entrant's termination cost is generally to its benefit and to the incumbent's detriment.
Keywords: L13; L51; L96; 330; Termination charges; Interconnection; Asymmetric Regulation; Price Discrimination; Telekommunikationspolitik; Netzzugang; Markteintritt; Kosten; Preisdifferenzierung; Theorie